REACTION OF THE RATS’ PALATAL GLAND’S DUCT SYSTEM ON THE INTRODUCTION OF METHACRYLATE - Timoshenko, Yu.V. (World of Medicine and Biology, 2016)
The aime of the researche was to determine the dynamics of changes in the ductal system of the palatine glands of rats after administration of epinephrine. Conducted morphometric study found that injection of adrenalin to rats causes a significant decrease in the metric values of the outer diameter of the excretory ducts on the 14th day of the experiment. Up to 30 days took a progressive decrease in the indicator in the ducts I and III and an increase in orders - in channels II order. The height of epithelial cells grown in the ducts and order and decreased - in channels II and III of the order on the 14th day of the experiment, 30 hours of observation - has decreased. Lumen diameter ducts palatal salivary glands decreased at all stages of monitoring. Set change due to both direct irritant effect of adrenaline on the rats, and the changes of blood supply to the mucosa, which leads to disruption of the flow system trophism palatine glands of rats.